2003
DOI: 10.1007/s00228-003-0631-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menthol on caffeine disposition and pharmacodynamics in healthy female volunteers

Abstract: Objectives: The present study was undertaken to determine whether a single oral dose of menthol affects the metabolism of caffeine, a cytochrome P 450 1A2 (CYP1A2) substrate, and pharmacological responses to caffeine in people. Methods: Eleven healthy female subjects participated in a randomized, double-blind, two-way crossover study, comparing the kinetics and effects of a single oral dose of caffeine (200 mg) in coffee taken together with a single oral dose of menthol (100 mg) or placebo capsules. Serum caff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, it did not affect the AUC. 4 Studies have also demonstrated menthol's potential to affect the cytochrome P450 system by inducing and inhibiting enzymes. In one report, oral administration of L-menthol to rats (800 mg/kg/day) induced CYP450 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it did not affect the AUC. 4 Studies have also demonstrated menthol's potential to affect the cytochrome P450 system by inducing and inhibiting enzymes. In one report, oral administration of L-menthol to rats (800 mg/kg/day) induced CYP450 enzymes.…”
Section: Discussionmentioning
confidence: 99%